The Role of Regional and State Initiatives in Nursing Home Advance Care Planning Policies - Fu, Caroline J. (Am J Hosp Palliat Care, 2020)
OBJECTIVE: Antibiotic use at the end of life (EoL) may introduce physiological as well as psychological stress and be incongruent with patients’ goals of care. Advance care planning (ACP) related to antibiotic use at the EoL helps improve goal-concordant care. Many nursing home (NH) residents are seriously ill. Therefore, we aimed to examine whether state and regional ACP initiatives play a role in the presence of “do not administer antibiotics” orders for NH residents at the EoL. METHODS: We surveyed a random, representative national sample of 810 U.S. NHs (weighted n=13,983). The survey included items on “do not administer antibiotics” orders in place and participation in infection prevention collaboratives. The survey was linked to state Physician Orders for Life-Sustaining Treatment (POLST) adoption status and resident, facility, and county characteristics data. We conducted multivariable regression models with state fixed effects, stratified by state POLST designation. RESULTS: NHs in mature POLST states reported higher rates of “do not administer antibiotics” orders compared to developing POLST states (10.1% vs. 4.6%, respectively, p=0.004). In mature POLST states, participation in regional collaboratives and smaller NH facilities (<100 beds) were associated with having “do not administer antibiotics” orders for seriously ill residents (β = 0.11, p=0.006 and □ = 0.12, p=0.003, respectively). DISCUSSION: NHs in states with mature POLST adoption that participated in infection control collaboratives were more likely to have “do not administer antibiotics” orders. State ACP initiatives combined with regional antibiotic stewardship initiatives may improve inappropriate antibiotic use at the EoL for NH residents.